Depolymerization of tubulin as the main molecular mechanism of the cytotoxic and antitumor activity of pyrrole-containing heterocyclic compounds - A. R. Galembikova; P. D. Dunaev; T. V. Ivoilova; A. I. Gilyazova; A. E. Galyautdinova; E. G. Mikheeva; S. S. Zykova; N. M. Igidov; P. B. Kopnin; S. V. Boichuk (Успехи молекулярной онкологии)
Introduction. Microtubules are highly dynamic polymers of α, β-tubulin dimers involves in a broad spectrum of the processes, such as intracellular transport and cell proliferation. This makes them an attractive molecular target for anti-cancer therapies. Substances that affect the dynamic state of tubulin microtubules are known as the mitotic poisons that are effectiveand widely used in the chemotherapy of various tumors. Mitotic poisons are able to interfere with polymerization (stabilization) or depolymerization of tubulin, which in turn leads to the arrest of cells in the M-phase (named as a mitotic catastrophe) and their subsequent death via activation of apoptotic mechanisms. However, the effectiveness of MP-based therapies is gradually decreasing over the time due to development of multiple drug resistance mechanisms in cancer cells. Thus, development of novel compounds selectively targeting tubulin and effectively overcoming multiple drugresistance phenotype in cancer is an urgent need in current oncology.   Aim. To examine the cytotoxic and antitumor activities of several pyrrole-containing heterocyclic compounds (EPC-91, EPC-92 and PCA-93) against cancer cell lines with epithelial and mesenchymal origin, including those with multiple drug resistance phenotype.   Materials and methods. Studies were performed on parental human cancer cell lines – triple-negative breast cancer HCC1806, gastrointestinal stromal tumor GIST T-1, osteosarcoma SaOS-2, – sensitive to chemotherapy (paclitaxel, doxorubicin) and their resistant sublines (HCC1806 Tx-R, GIST T-1 Tx-R, SaOS-2 Dox-R), as well as on murine colorectal adenocarcinoma cell line Colon-26, exhibiting primary resistance to the aforementioned chemotherapeutic agents.   Results. The cytotoxic activities of EPC-91 and PCA-93 were due to their abilities to depolymerize tubulin. The results of immunofluorescence microscopy and Western blotting indicated that the compounds disrupt assembly of tubulin microtubules and prevent polymerization of α-tubulin in cancer cells. Inhibition of tubulin polymerizations led to significant increasein number of round-shaped and phospho-histone 3 (e. g. mitotic) cells, followed by their death through apoptosis. PCA-93 also exhibited potent anti-tumor effect against Colon-26 cells due to its anti-proliferative and proapoptotic activities.   Conclusion. The data shown here illustrates potent cytotoxic activities of EPC-91 and PCA-93 against multiple cancer cell lines in vitro including those with multiple drug resistance phenotype. Similarly, PCA-93 was found to be highly effective against Colon-26 cell in vivo, thereby illustrating the attractive platform for the development of novel pyrrole-based agents exhibiting potent anti-tumor activities.